2010
DOI: 10.1002/pssb.200945549
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical route to thermoelectric nanowires via organic electrolytes

Abstract: International audienceThermoelectric nanowires have been predicted to have superior properties compared to their bulk counterparts due to quantum confinement. We present the synthesis of chalcogenide nanowires A2B3 (A¼Bi, Sb; B¼S, Se, Te) and PbB (B¼S, Se, Te) by electrochemical deposition into highly ordered porous Al2O3 membranes. The narrow pore size distribution of the templates reproducibly yields very homogeneous nanowires upon electrodeposition into the pores. The thermoelectric nanowires presented here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Nanoporous anodic Al 2 O 3 films, obtained by the simple and inexpensive technique for two-step anodization of high-purity Al substrates (Masuda and Fukuda, 1995;Masuda and Satoh, 1996), have attracted huge interest and have been used as templates for the synthesis of a wide range of nanomaterials (Eftekhari, 2008;Lupu, 2010;Nalwa, 2011), including ordered arrays of magnetic nanowires Vázquez et al, 2005;Prida et al, 2007;Klammer et al, 2010), nanoparticles (Gultepe et al, 2007;Badini et al, 2011), nanotubes (Imai et al, 1999;Daub et al, 2007;Zierold et al, 2011;Proença et al, 2013) arrays of antidots (Masuda and Fukuda, 1995;Vázquez et al, 2008;López-Antón et al, 2009;Béron et al, 2011;Merazzo et al, 2012). Anodization of Al consists of the anodic oxidation of an Al electrode under wellcontrolled electrochemical conditions.…”
Section: Mild Anodizationmentioning
confidence: 99%
“…Nanoporous anodic Al 2 O 3 films, obtained by the simple and inexpensive technique for two-step anodization of high-purity Al substrates (Masuda and Fukuda, 1995;Masuda and Satoh, 1996), have attracted huge interest and have been used as templates for the synthesis of a wide range of nanomaterials (Eftekhari, 2008;Lupu, 2010;Nalwa, 2011), including ordered arrays of magnetic nanowires Vázquez et al, 2005;Prida et al, 2007;Klammer et al, 2010), nanoparticles (Gultepe et al, 2007;Badini et al, 2011), nanotubes (Imai et al, 1999;Daub et al, 2007;Zierold et al, 2011;Proença et al, 2013) arrays of antidots (Masuda and Fukuda, 1995;Vázquez et al, 2008;López-Antón et al, 2009;Béron et al, 2011;Merazzo et al, 2012). Anodization of Al consists of the anodic oxidation of an Al electrode under wellcontrolled electrochemical conditions.…”
Section: Mild Anodizationmentioning
confidence: 99%
“…By using both type of templates, different thermoelectrics have been prepared by electrodeposition [165,166] from water solution or using organic solvents like dimethyl sulfoxide (DMSO), such as Bi [167], Bi 1−x Sb x [168,169], Bi 2 Te 3 [161,[170][171][172][173][174][175][176][177][178][179], Bi 2 (TeSe) 3 [180], Sb 2 Te 3 , PbTe, (BiSb) 2 Te 3 [181,182], PbSe [183], PbSe 1−x Te x , CoSb 3 , and Bi 2 Te 3 /Sb [184] and Bi 2 Te 3 /(Bi 0.3 Sb. 0.7 ) 2 Te 3 superlattice NWs [185].…”
Section: Bottom-upmentioning
confidence: 99%
“…In 2010, Nielsch's group (Klammer et al, 2010) reported the electrodeposition of antimony telluride nanowires grown in an organic solvent (ethylene glycol) using constant current density and 50 nm pore diameter alumina. The Seebeck coefficient was found to be 21 μV/K.…”
Section: Thermoelectric Propertiesmentioning
confidence: 99%